2017
DOI: 10.1063/1.4982216
|View full text |Cite
|
Sign up to set email alerts
|

Grafted polymer chains suppress nanoparticle diffusion in athermal polymer melts

Abstract: We measure the center-of-mass diffusion of poly(methyl methacrylate) (PMMA)-grafted nanoparticles (NPs) in unentangled to slightly entangled PMMA melts using Rutherford backscattering spectrometry. These grafted NPs diffuse ∼100 times slower than predicted by the Stokes-Einstein relation assuming a viscosity equal to bulk PMMA and a hydrodynamic NP size equal to the NP core diameter, 2R = 4.3 nm. This slow NP diffusion is consistent with an increased effective NP size, 2R ≈ 20 nm, nominally independent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…The model and method derivations follow closely those of our previous works for both the SCFT ,, and DMFT ,, methods. We place an explicit particle grafted with A- and B-type discrete Gaussian polymer chains in an explicit solvent, S, as shown in Figure a.…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…The model and method derivations follow closely those of our previous works for both the SCFT ,, and DMFT ,, methods. We place an explicit particle grafted with A- and B-type discrete Gaussian polymer chains in an explicit solvent, S, as shown in Figure a.…”
Section: Methodsmentioning
confidence: 65%
“…Furthermore, the previous studies used a mean-field approximation, even for the systems in solution, where it is understood that fluctuations are prominent and that the mean-field approximation is inaccurate. 28 Here, we investigate the effects of fluctuations and of nonuniform grafting site distributions on the brush structure of a single particle using a combination of SCFT and a fluctuating dynamic mean-field theory [29][30][31]. The DMFT method used in this study is similar to the MC-SCMF model used to study planar mixed brushes with the small caveat that we use Langevin dynamics rather than Monte Carlo moves to update the particle positions; this is largely irrelevant in the analysis of equilibrium phenomena.…”
mentioning
confidence: 99%
“…Most often, GNPs are dispersed in a matrix of polymer chains or oligomers having the same chemistry as the grafted chains. Several theoretical, experimental, and computational approaches have been used in the last 30 years to investigate the structural properties and dynamics of these systems. …”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Zhao et al, the two critical variables in the context of this study are the NP diffusion rate and the rate of polymer crystallization, that is, nucleation and growth rates. There are several groups working on the former topic, namely, the diffusion of NPs and polymers in a nanocomposite, and we specifically highlight the experimental works of Composto and Winey et al , and the recent theoretical work of Ge et al It was experimentally shown that, while the formation of a physically adsorbed polymer layer slowed down NP diffusion, NPs chemically grafted with a dense polymer brush were slowed even more significantly. Importantly, in the latter case, the results were independent of grafting density (over a relatively large range) in the dense brush range.…”
Section: Introductionmentioning
confidence: 99%